FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA GURU DALAM MENJALANKAN TUGAS DI SDN 001 TERATAK KECAMATAN RUMBIOJAYA - Fitriani, Arida; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Teachers are human elements that determine the success of education. Profession asa teacher relates to students, who naturally have similarities and differences. Serve thediverse task requires patience and diligence are very high, especially when dealing withyoung learners. This study aims to determine the factors that affect the performance ofteachers in performing their duties in SDN 001 Teratak subdistrict Rumbio Jaya. This studywas conducted in April 2014 by an interview of the entire teaching staff at the SDN 001Teratak. Moreover, the authors also observed the teaching and learning process as well asliterature on the results of previous studies are considered relevant. The results showed thatthe factors that affect the performance of teachers at SDN 001 Teratak is teachermotivation in work, workplace atmosphere, discipline and welfare of teachers. Having donepartial test (t test) against these four factors, the variables of teacher motivation has asignificant influence on the performance of the teacher about 2,799 (279,9%) . While theother variables are not significant. But when done simultaneously testing (test f) thevariable of teacher motivation in work, workplace atmosphere, discipline and welfare ofteachers working together to have significant influence on the performance of teachers atSDN 001Teratak about 57,3%.